1999
DOI: 10.1021/la980795b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tail-Group Hydrogen Bonding on the Stabilities of Self-Assembled Monolayers of Alkylthiols on Gold

Abstract: Self-assembled monolayers (SAMs) of alkylthiols with polar terminal groups on gold may be photopatterned to produce structures that are stable against displacement by methyl-terminated thiols with longer alkyl chains. For example, 3-mercaptopropanoic acid (MPA) patterns are not eroded by octadecanethiol (ODT). However, photopatterned SAMs of methyl-terminated thiols shorter than tetradecanethiol are eroded by exposure to solutions of thiols with polar terminal groups. For example, dodecanethiol (DDT) patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
129
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(142 citation statements)
references
References 34 publications
10
129
3
Order By: Relevance
“…Heating this ordered overlayer can cause the individual strands of the formate to interact with each other on bending. The terminal H atoms can react with other terminal H atoms to form H 2 as has been observed in the study of self assembled monolayers [9][10][11]. We have observed coincident H 2 and CO 2 evolution at 440 K from an overlayer of formate species at 80 % of saturation [12], suggesting that the self assembled monolayer mechanism could operate under these conditions.…”
Section: Introductionsupporting
confidence: 72%
“…Heating this ordered overlayer can cause the individual strands of the formate to interact with each other on bending. The terminal H atoms can react with other terminal H atoms to form H 2 as has been observed in the study of self assembled monolayers [9][10][11]. We have observed coincident H 2 and CO 2 evolution at 440 K from an overlayer of formate species at 80 % of saturation [12], suggesting that the self assembled monolayer mechanism could operate under these conditions.…”
Section: Introductionsupporting
confidence: 72%
“…This explanation is supported by studies of Cooper and Leggett [31], who photopatterned SAMs of alkylthiols with polar terminal groups on gold are to produce structures that are stable against displacement by methyl-terminated thiols with longer alkyl chains. For example, MPA patterns are not eroded by octadecanethiol [31]. Our experiments are in agreement with these observations and the results suggest that the amount of DDT adsorbed by the exchange of MPA is negligible in comparison by the amount of DDT immobilization on bare gold areas which have been created deliberately by selective reductive desorption of MPA.…”
Section: Formation Of Mixed Monolayersmentioning
confidence: 80%
“…Our data seems to have a relation with previous reports in which the authors observed that interaction between hydroxyl groups via hydrogen bonding leads to a higher stabilization of the self-assembled monolayer. 67,68 …”
Section: Application: Molecular Adsorption Sensingmentioning
confidence: 99%